Decentralized autonomous organization design for the commons and the common good - Van Vulpen, Paul; Jansen, Slinger (Frontiers in Blockchain, 2023)
The current internet economy is characterised by a historically unprecedented bundling of private sector power over infrastructures. This situation is harmful for overcoming problems where collective action is needed, such as for governing digital commons. Organisations that run on collectively owned decentralised infrastructure are able to overcome this centralisation of power. These common decentralised autonomous organisations (DAOs) could help in fostering digitally enabled collective action.However, currently we have no clear view of how a DAO designed for commons governance would operate and be governed. By creating a conceptual prototype of a DAO governing a common, we provide a clear path of how common DAOs should mature and which tools are needed to create them.In this research, we created a governance framework for common DAOs by combining 16 works on technology for commons governance. The framework reveals that common DAO governance consists of three areas: 1) Governance structure, 2) Enabling technology, and 3) Community governance. We provide governance mechanisms that together describe an implementation of Ostrom's common governance principles in a DAO.This work is a synthesis of previous research on technology for collective action. The proposed framework aids in standardising DAO governance for the common good and may contribute to a large scale roll-out of commons DAOs.